The effect of parameters of group consolidation based on live weight and growth uniformity on growth dynamics in young pigs - Пелих, В. Г. (Scientific Progress & Innovations, 2014)
The paper studied the effect of equalization of groups of pigs on live weight at weaning from the sow and uniformity parameter growth in the suckling period on productive qualities of pigs. Proved a significant influence of these parameters on the dynamics of daily average and relative growth and variability of live weight of pigs. The data obtained should be used for breeding plants , reproducers and commercial farms for the optimal set of groups of pigs , increasing the energy of their growth in growing and fattening and obtain a homogeneous product .